STRATEGI MARKETING PUBLIC RELATIONS DALAM MENUMBUHKAN LOYALITAS NASABAH PERUSAHAAN ASURANSI JIWA - Hendri Prasetya; Dinda Ashriah Rahman (Jurnal Pustaka Komunikasi, 2020)
AJB Bumiputera 1912 is an insurance that has been established since 1912 and still survives today. To grow customer loyalty among the many insurance competitions, this insurance uses a marketing public relations strategy. This research aims to find out the Marketing Public Relations Strategy in fostering Customer Loyalty of AJB Bumiputera 1912 branch of Wolter Monginsidi in Jakarta. This research uses qualitative research approaches that are qualitative descriptions, and constructivism paradigms, with case study techniques and in-depth interviews and triangulation to determine the validity of data. In conducting research, AJB Bumiputera 1912 branch of Wolter Monginsidi Jakarta used 4 Steps to design Public Relations activities and used pencils theory in conducting Marketing Public Relations strategy. Research findings show Marketing Public Relations Strategy, AJB Bumiputera 1912 wolter monginsidi branch has been running marketing public relations strategy in the form of Publications and publicity, Event, News, Community Involvement, Inform or Lobbying or negotiating (approach and negotiating), Social Responsibility.